2014
DOI: 10.4314/ahs.v14i3.22
|View full text |Cite
|
Sign up to set email alerts
|

B1 but not B2 bradykinin receptor agonists promote DU145 prostate cancer cell proliferation and migration

Abstract: Background: The kallikrein-kinin system (KKS) is an endogenous pathway involved in angiogenesis and tumourigenesis, both vital for cancer growth and progression. Objectives: To investigate the effect of two bradykinin receptor (B1R and B2R) agonists on growth and motility of prostate tumour (DU145) and micro-vascular endothelial cells (dMVECs). Methods: Increasing concentrations of selective B1R and B2R agonists were added to cultured cells. Cell proliferation and migration were assessed using the 3-[4,5 dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…BK exhibits potent cardioprotective and hypotensive effects and with its metabolites is crucial for the treatment of type 2 diabetes mellitus and glioblastoma . The bradykinin receptors B1R and B2R are important targets for the development of alternative approaches to prostate cancer therapy . Thus, in this context, BK appears to be a good model molecule demonstrating applicability of uniformly deuterated peptides for quantitative liquid chromatography/mass spectrometry (LC/MS) analysis of peptides and their degradation metabolites.…”
mentioning
confidence: 99%
“…BK exhibits potent cardioprotective and hypotensive effects and with its metabolites is crucial for the treatment of type 2 diabetes mellitus and glioblastoma . The bradykinin receptors B1R and B2R are important targets for the development of alternative approaches to prostate cancer therapy . Thus, in this context, BK appears to be a good model molecule demonstrating applicability of uniformly deuterated peptides for quantitative liquid chromatography/mass spectrometry (LC/MS) analysis of peptides and their degradation metabolites.…”
mentioning
confidence: 99%
“…Apparently, stimulation of BDKRB1 produces opposite effects on cell migration depending on the cell type involved. Whereas BDKRB1 promotes cell migration in some cancer cells, and human neutrophils , it inhibits migration of vascular smooth muscle and dendritic cells . Our in vitro experiments indicate that LDBK produces weak keratinocyte migration and pretreatment of cells with 1 n m LDBK delays keratinocyte migration induced by EGF, suggesting that BDKRB1 may negatively modulate EGFR action during wound healing.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, we believed that at least in our experiments, BK had a beneficial effect on the prostate by promoting the production of NO via vascular endothelium, and because of its rapid degradation, BK did not obviously cause the proliferation or contraction of rat prostate stromal cells in vivo . Additionally, Naidu et al indicated that BK could mediate metastasis and invasion of the prostate cancer cells, even associated with angiogenesis [ 42 ]. However, in benign cases, the benefits and disadvantages of KKS for the prostate are worthy of discussion.…”
Section: Discussionmentioning
confidence: 99%